Protocol for tumour-focused dose-escalated adaptive radiotherapy for the radical treatment of bladder cancer in a multicentre phase II randomised controlled trial (RAIDER): radiotherapy planning and delivery guidance. Issue 12 (31st December 2020) - Hafeez, Shaista; Webster, Amanda; Hansen, Vibeke N; McNair, Helen A; Warren-Oseni, Karole; Patel, Emma; Choudhury, Ananya; Creswell, Joanne; Foroudi, Farshad; Henry, Ann; Kron, Tomas; McLaren, Duncan B; et al.
Abstract : Introduction: Daily radiotherapy delivered with radiosensitisation offers patients with muscle invasive bladder cancer (MIBC) comparable outcomes to cystectomy with functional organ preservation. Most recurrences following radiotherapy occur within the bladder. Increasing the delivered radiotherapy dose to the tumour may further improve local control. Developments in image-guided radiotherapy have allowed bladder tumour-focused 'plan of the day' radiotherapy delivery. We aim to test within a randomised multicentre phase II trial whether this technique will enable dose escalation with acceptable rates of toxicity. Methods and analysis: Patients with T2-T4aN0M0 unifocal MIBC will be randomised (1:1:2) between standard/control whole bladder single plan radiotherapy, standard dose adaptive tumour-focused radiotherapy or dose-escalated adaptive tumour-focused radiotherapy (DART). Adaptive tumour-focused radiotherapy will use a library of three plans (small, medium and large) for treatment. A cone beam CT taken prior to each treatment will be used to visualise the anatomy and inform selection of the most appropriate plan for treatment. Two radiotherapy fractionation schedules (32f and 20f) are permitted. A minimum of 120 participants will be randomised in each fractionation cohort (to ensure 57 evaluable DART patients per cohort). A comprehensive radiotherapy quality assurance programme including pretrial and on-trial components is instituted to ensure standardisation of radiotherapy planning and delivery. The trial has a two-stage non-comparative design. The primary end point of stage I is the proportion of patients meeting predefined normal tissue constraints in the DART group. The primary end point of stage II is late Common Terminology Criteria for Adverse Events grade 3 or worse toxicity aiming to exclude a rate of >20% (80% power and 5% alpha, one sided) in each DART fractionation cohort. Secondary end points include locoregional MIBC control, progression-free survival overall survival and patient-reported outcomes. Ethics and dissemination: This clinical trial is approved by the London-Surrey Borders Research Ethics Committee (15/LO/0539). The results when available will be disseminated via peer-reviewed scientific journals, conference presentations and submission to regulatory authorities. Trial registration number: NCT02447549; Pre-results